Uma maneira de proteger e educar : a Casa Maternal Amélia Leite (1947-1970) - Lima, Solyane Silveira (2009)
This study aims to investigate the creation and consolidation of Protection Society of Casa Maternal Amélia Leite , in the period that includes the opening date in 1947 until 1970, when its founder, the doctor Augusto César Leite, get away from the direction. Formulated from the hygienists precepts, this philanthropic and educational institution, that service to single adolescent mothers and children, use to promote medical social assistance and moralizing education with the objective of reducing the number of abortions, infanticides and prostitution in Sergipe. To better understand its dynamic, operation and contribution, theoretical methodological subsidies were sought in the New Cultural History and in the contributions of Michel Foucault, Norbert Elias and Pierre Bourdieu. In addition to, it was tried to elucidate the initiatives related to the issues of the devoid child, aiming to contribute to studies about the History of Childhood and Education in Sergipe.